Moral-psychological mechanisms of rebound effects from a consumer-centered perspective: A conceptualization and research directions - Reimers, Hanna; Lasarov, Wassili; Hoffmann, Stefan (Frontiers in Psychology, 2022)
Rebound effects on the consumer level occur when consumers’ realized greenhouse gas emission savings caused by behaviors that might be beneficial to the environment are lower than their potential greenhouse gas emission savings because the savings are offset by behavioral adjustments. While previous literature mainly studied the economic mechanisms of such rebound effects, research has largely neglected the moral-psychological mechanisms. A comprehensive conceptualization of rebound effects on the consumer level can help fill this void and stimulate more empirical research in this relevant area. To this end, the paper introduces three focal dimensions of rebound effects on the consumer level: mechanism of rebound effects, product category, and consumption context. Based on this conceptualization, and integrating assumptions from the theory of moral licensing, the theory of categorization, and the construal level theory, this paper further refines the conceptualization of the moral component as an explanatory factor for rebound effects and highlights that the moral-psychological mechanisms of indirect rebound effects (i.e., rebound effects that occur across different product categories or consumption contexts) are more complex and diverse than the economic mechanisms. The paper outlines promising directions for future studies considering the different quantification and characteristics of economic and moral currencies that explain rebound effects on the consumer level and the strategic categorization of products and consumption contexts.